The Basic Elements and Their Proper Balance in the Curriculum of a Collegiate Business School - Hotchkiss, Willard E. (Journal of Political Economy, 1920)
Note.–This number of the Journal of Political Economy is given over to the leading papers and discussions of the first meeting of the Association of Collegiate Schools of Business which was held at Harvard University, November 13, 14, and 15, 1919. It is a matter of regret that illness prevented Dean Herman Schneider, of the University of Cincinnati, from preparing for publication his paper on "The Coordination of Business and Engineering Courses."